Phytosanitary certification of the Alliance of Bioversity International and CIAT germplasm health laboratory - Cuervo Ibáñez, Maritza; Ramírez Pretelt, Julio César; Niño, D.P.; Gutiérrez, A.; González, L.J. (2022)
Plant Health 2022, Pittsburgh, Pennsylvania, USA. August 6-10, 2022.